2017
DOI: 10.1080/15284336.2016.1251030
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life improvement in HIV-1 patients treated with raltegravir in a real-life observational study: RACING

Abstract: Patient QoL improved significantly over a 24-month period of treatment with a raltegravir-containing regimen. FIS and HSI are sensitive tools to measure the impact of new antiretroviral combinations on a patient's perception of QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In a study conducted in high and middle income countries comparing LPV/r + RAL versus LPV/r + NRTIs for second-line ART, QoL (physical and mental domains) also improved in both treatment arms after one year with no difference between arms [16]. Other observational studies in high income settings have described improvements in QoL after one year of PI-containing ART [14] and over a 24-month period of treatment with a RAL-containing regimen [15]. In a randomized clinical trial conducted in Spain evaluating the use of either a PI or EFV based second-line regimen among participants who failed a PI-containing first-line regimen, QoL increased in both arms although it increased more for those in an EFV-containing versus PI-containing second-line regimen [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in high and middle income countries comparing LPV/r + RAL versus LPV/r + NRTIs for second-line ART, QoL (physical and mental domains) also improved in both treatment arms after one year with no difference between arms [16]. Other observational studies in high income settings have described improvements in QoL after one year of PI-containing ART [14] and over a 24-month period of treatment with a RAL-containing regimen [15]. In a randomized clinical trial conducted in Spain evaluating the use of either a PI or EFV based second-line regimen among participants who failed a PI-containing first-line regimen, QoL increased in both arms although it increased more for those in an EFV-containing versus PI-containing second-line regimen [30].…”
Section: Discussionmentioning
confidence: 99%
“…QoL at first-line ART initiation in resource-limited settings (RLS) has varied with disease severity, demographic characteristics and country [3, 10, 11] and it improves over time after starting ART [10–13]. Previous studies have shown improvements in QoL among HIV-infected individuals taking PI-containing regimens [14] and among individuals taking a raltegravir-containing regimen [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Poorer PROs in older patients has been reported in many studies on HCV treatment, including the most-recent ones with highly effective and very well tolerated direct-acting antiviral regimens 20. Older age was negatively associated with physical Fatigue Impact Scale subscores in an observational study on raltegravir 19, while in a review of literature, there was no association between age and fatigue in most studies 21. HIV disease factors, such as CDC stage, CD4 and plasma HIV RNA did not influence PROs improvement, indicating that benefit of HIV therapy on quality of life was seen whatever the baseline immune-virological status of the patient, taking into account that 15 patients in our study had CD4 cell counts< 200/mm3 and only 5% CDC stage C HIV infection.…”
Section: Discussionmentioning
confidence: 90%
“…Some putative mechanisms may be related to the improvement of cytokine and other metabolites profile, both in peripheral blood and central nervous system, due to the viral suppression which could in turn positively impact patients’ experience 18. Viral suppression might thus improve fatigue and other PROs related to chronic HIV infection 19.…”
Section: Discussionmentioning
confidence: 99%